Design of cissus–alginate microbeads revealing mucoprotection properties in anti-inflammatory therapy (2015)
Cissus gum has been employed as polymer with sodium alginate in the formulation of diclofenac microbeads and the in vivo mucoprotective properties of the polymer in anti-inflammatory therapy assessed in rats with carrageenan-induced paw edema in comparison to diclofenac powder and commercial diclofenac tablet. A full 23 factorial experimental design has been used to investigate the influence of concentration of cissus gum (X1); concentration of calcium acetate (X2) and stirring speed (X3) on properties of the microbeads. Optimized small discrete microbeads with size of 1.22 ± 0.10 mm, entrapment efficiency of 84.6% and t80 of 15.2 ± 3.5 h were obtained at ratio of cissus gum:alginate (1:1), low concentration of calcium acetate (5% w/v) and high stirring speed (400 rpm). In vivo studies showed that the ranking of percent inhibition of inflammation after 3 h was diclofenac powder > commercial tablet = cissus > alginate. Histological damage score and parietal cell density were lower while crypt depthand mucosal width were significantly higher (p < 0.05) in the groups administered with the diclofenac microbeads than those administered with diclofenac powder and commercial tablet, suggesting the mucoprotective property of the gum. Thus, cissus gum could be suitable as polymer in the formulation of non-steroidal anti-inflammatory drugs ensuring sustained release while reducing gastric side effects.